Functional Role of Interjections of Tatar Language - Husnutdinov, Damir Haydarovich; Sagdieva, Ramilya Kamilovna; Mirzagitov, Ramil Hamitovich; Karipzhanova, Gulnaz Tokenovna (International Journal of Criminology and Sociology, 2022)
Recently, in studying the linguistic picture of the world, interest has been growing in the national originality of the perception of reality, the national specificity of the reflection of the world picture in the language. The linguistic picture of the world is not linguistic; it reflects cognitive reality due to history, culture, geography, and other factors within the objective world. This article, based on such general scientific research methods as induction, deduction, observation, analysis, and synthesis of empirical material, attempts to reveal the national identity of the emotional experiences of the Tatar people. The study’s subject is the emotive lexicatic language, which makes it possible to formulate and evaluate the presented picture and conceptualization of the surrounding Tatars. As the results of this study confirm, a person in the Tatar language picture of the world and eastern linguistic culture is less dualistic than a European; his emotions and speech tend to be in harmony, mutually complementing each other. In life, in everyday life, and the feelings of the Tatars, there is a severe imprint of the traditions and canons of Islam. The importance of the study of emotive vocabulary lies in the fact that it allows you to identify the priorities of the Tatar language consciousness, as well as the features of the vision of the Tatars world, the representation of the image of a person and his world from the position of the universal in the phraseology of the Tatar language, and the position of national specific features. The study of the dynamic semantics of phraseological units of the Tatar language in the structure of meaning makes it possible to represent significance for the general theory of linguistic science.